Energy performance and flow characteristics of a multiphase pump with different tip clearance sizes. (January 2019) - Zhang, Jinsong; Fan, Honggang; Zhang, Wei; Xie, Zhifeng
Deep sea oil resources worldwide possess great potential for exploration; however, multiphase medium technology requires urgent development. The multiphase pump has achieved great success as one of the most advanced machinery in underwater oil and gas exploration. Tip clearance is inevitable between the rotating and stationary components of the multiphase pump. In this study, tip clearance sizes of 0.0, 0.2, 0.5, and 0.8 mm are selected to investigate the effect of tip clearance on energy performance and flow characteristics of a multiphase pump. Results show that pressure rises decrease by 10.72%, 24.96%, and 41.39% with gas volume fraction = 0% under different tip clearance sizes, while the pressure rises decrease by 17.10%, 25.35%, and 38.11% with gas volume fraction = 10%. The dominant frequencies and maximum amplitudes of pressure fluctuation rise with the increase in tip clearance. The entrainment effect between the tip leakage flow and main flow in the impeller strengthens with the increase in tip clearance size; the induced vortex area and leakage flow rate also increase.